Decades of discovery: unveiling emerging trends, pivotal research areas, and landmark publications in national tobacco research in India - Singh, Alok; Kashyap, Akanksha; Varshney, Saurabh; Bhattacharya, Sudip (Frontiers in Research Metrics and Analytics, 2025)
IntroductionTobacco use remains a major public health concern in India, contributing significantly to the burden of non-communicable diseases and premature mortality. Over the past two decades, national tobacco research has evolved in response to shifting regulatory frameworks, scientific developments, and increasing awareness of tobacco's health, social, and environmental implications. The World Health Organization Framework Convention on Tobacco Control (WHO FCTC), adopted in 2003, has played a catalytic role in aligning research efforts with global priorities. However, there is a need to map the growth and direction of this research to identify strengths, gaps, and emerging trends within the Indian context.MethodsA bibliometric analysis was conducted to evaluate tobacco-related research output affiliated with Indian institutions between 2003 and 2024. Data were retrieved from the SCOPUS database, limited to peer-reviewed journal articles and reviews published in English. Analytical tools included SCOPUS Analytics, Microsoft Excel, the Biblioshiny package in R, and VOS viewer software. These tools were used to extract and visualize trends in publication volume, subject categories, key authors, institutional collaborations, citation metrics, and thematic hotspots. Inclusion criteria were confined to Indian-affiliated institutions contributing to national and global discourse on tobacco research.ResultsTobacco research in India showed a consistent upward trend post-2003, with notable surges corresponding to key public health developments. The majority of publications were concentrated in the domain of medicine, particularly focusing on cancer prevention and tobacco control interventions. Leading contributors included institutions such as the All India Institute of Medical Sciences (AIIMS), with significant collaborations observed with United States-based researchers. Despite increased output, research on the social and environmental consequences of tobacco use remained limited. Additionally, international collaboration was relatively low, and funding was primarily from Indian agencies, with minimal support from global or low-income country partnerships. Notably, recent studies employed advanced methodologies, such as machine learning and nanotechnology, and examined newer themes like the intersection of tobacco use and COVID-19-related respiratory risks.DiscussionThe findings indicate a maturing research ecosystem around tobacco in India, strongly anchored in biomedical science and policy interventions. However, the underrepresentation of interdisciplinary studies exploring socio-cultural and ecological dimensions suggests a critical gap. Moreover, the low levels of international collaboration and inadequate funding for low-income contexts highlight systemic limitations that could hinder progress. To advance tobacco research nationally and globally, enhanced collaboration across disciplines and geographies is essential. Incorporating emerging technologies and focusing on equity-driven research agendas will be pivotal in addressing the multifaceted impact of tobacco use.